Opinions of physical education teachers about competencies of adminisrators on change management in educational institutions ın Turkey - Karakaya, Yunus Emre (Editura Universitatii din Pitesti, 2014)
Nowadays the process of rapid change affects education as well as many areas. This process of change requires the need to review some factors again such as educational institutions, management activities, teaching and learning activities, and school-environment relations. This study is aimed to determine the competencies of administrators on change management in accordance with the opinions of physical education teachers in educational institutions in Turkey. The sample group of the study consists of 220 physical education teachers from primary and secondary education schools. In this study the form of scale, developed by Göksoy (in 2010), was used to obtain views of the sample group. At the end of the study, some significant differences were found in the sub-component of communication in terms of gender and age variables. Some significant differences were found in the sub-components of communication, facilitation and support and vision in terms of tenure variable. No significant differences were found in the sub-components of “Education and Participation to Decision Making” with regards to the variables. In conclusion, administrators, teachers and other employees should be taken into the process of change through in-service trainings, seminars, and courses so that they would develop feeling of seeing themselves as part of a team. © JPES. All rights reserved.
Keywords: Attitude; Institutionalised elderly; Motivation; Physical activity